Identification of Antibiotic Resistance Gene to Amoxicillin in River: As a Proof of Concept toward AMR Pollution - Izzati, Nurul; Komarudin, Nurul Amri; Hasdayanti, Sri; Aprilia, Maya (International Journal of Biosciences and Biotechnology; Vol 12 No 1 (2024): International Journal of Biosciences and Biotechnology, 2025)
Antimicrobial Resistance burdens almost all nations, ranking among the top 10 threats identified by the World Health Organization. The transmission of AMR in the environment presents a dimension of lacking data in Indonesia, especially regarding rivers. AMR distribution in rivers is facilitated by antibiotic-resistant genes, and these genetic materials can be transferred to other microorganisms in the water. The mutated penicillin-binding protein 1A (pbp1a) is one of the genes that plays a role in amoxicillin resistance. It is well-documented that amoxicillin is one of the most prescribed antibiotics in primary healthcare settings, including in Sumbawa. Therefore, this study aims to identify the pbp1A gene in the Brang Biji river, Sumbawa, as a proof of concept for ARG transmission in water surfaces. The study found that more than 300,000 CFU/mL colonies grew on agar medium with 0.5 mg/mL amoxicillin at sites downstream of hospital WWTP effluent, followed by a decrease to around 50,000 CFU/mL further downstream. Two colonies, one white and one cream-colored, were susceptible to amoxicillin based on disk diffusion antimicrobial susceptibility tests. Moreover, both white and cream colonies were found to carry the mutated pbp1A gene according to the PCR method. This preliminary study can serve as valuable information for further analysis and more comprehensive research.